IMPACT INTERACTION SHORT CIRCUIT FROM REYKOVOYUKOLIYEYU NEAR BUTT TYPE INEQUALITY "GAP" IN THE PARAMETRIC SUBPAR DYNAMIC MODEL - , В. П., А. В., Г. О. (Municipal economy of cities. Series: «Economy science», 2013)
Investigated and determined the parameters of the shock interaction tram carriage of railway tracks including operational, mechanical and geometrical characteristics of the vehicle and load wagon variants. We consider the most common joints tram rail lines such as "gap."